In Sickness and in Health: The Oxygen Reactive Species and the Bone - Reis, Joana; Ramos, António (Frontiers in Bioengineering and Biotechnology, 2021)
Oxidative stress plays a central role in physiological and pathological bone conditions. Its role in signalment and control of bone cell population differentiation, activity, and fate is increasingly recognized. The possibilities of its use and manipulation with therapeutic goals are virtually unending. However, how redox balance interplays with the response to mechanical stimuli is yet to be fully understood. The present work summarizes current knowledge on these aspects, in an integrative and broad introductory perspective.